1993
DOI: 10.1557/proc-333-437
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Uranium-Bearing Phases in Soils From Fernald

Abstract: Electron beam techniques have been used to characterize uranium-contaminated soils at the Fernald Site, Ohio. Uranium particulates have been deposited on the soil through chemical spills and from the operation of an incinerator plant on the site. The major uranium phases have been identified by electron microscopy as uraninite, autunite, and uranium phosphite [U(PO3)4]. Some of the uranium has undergone weathering resulting in the redistribution of uranium within the soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…In contrast to the dominance of a single oxidation state, there is wide variability in the speciation of the hexavalent uranium from site to site and in some cases with depth at a given site. Microscopy and spectroscopy results further demonstrate considerable mineralogical heterogeneity (Buck et al, 1994;1995;Bertsch et al, 1994). Uranium-bearing phases…”
Section: Characterizing S O U Contaminatedmentioning
confidence: 93%
“…In contrast to the dominance of a single oxidation state, there is wide variability in the speciation of the hexavalent uranium from site to site and in some cases with depth at a given site. Microscopy and spectroscopy results further demonstrate considerable mineralogical heterogeneity (Buck et al, 1994;1995;Bertsch et al, 1994). Uranium-bearing phases…”
Section: Characterizing S O U Contaminatedmentioning
confidence: 93%
“…Characterization studies at DOE sites, such as the Hanford, Fernald, Oak Ridge, and Savannah River Sites, suggest that sediments and soils contaminated from disposal or spills of uranium-containing liquid wastes at these sites can contain uranium-containing minerals or coprecipitates [e.g., Zachara and coworkers. (2002a); Serne et al (2002); Delegard et al (1986); Buck et al (1994Buck et al ( , 1996; Morris et al (1996); Roh et al (2000); Bertsch et al (1994); and Hunter and Bertsch (1998)].…”
Section: Solubilitymentioning
confidence: 99%
“…At the time of the studies by Delegard et al (1986), the uranium in these sediments had been remobilized by water flow resulting from nearby disposal of cooling water. Buck (1994Buck ( , 1996 used analytical electron microscopy (AEM) combined with electron diffraction to identify meta-autunite [Ca(UO 2 ) 2 (PO 4 ) 2 •2-6H 2 O], uraninite, and uranium metaphosphate [U(PO 3 ) 4 ] in uranium-contaminated soils from the DOE former uranium production facility at Fernald, Ohio. Morris et al (1996) determined the presence of autunite-like a and schoepite-like mineral phases in uraniumcontaminated soils from Fernald.…”
Section: Solubilitymentioning
confidence: 99%
“…These results indicated that characterization by electron microscopy would be representative, as all the contamination was in particulate form. Buck et al [2,7,8], using electron microscopy techniques, also confirmed that most uranium in incinerator and SP2 soils was in the form of discrete particles but were unable to locate many uranium-bearing particles in SP4 soil samples.…”
Section: Other Characterization Studies At the Fernald Environmental mentioning
confidence: 99%